North-American free trade agreement : the elements involved. - Hart, Michael (1991)
Agrees that the basis for an economically and politically sound agreement appears to be present, and that the idea of a North American free trade agreement appears to enjoy broad support in the USA, Mexico and Canada. Points out that there are several issues, some of which are extremely difficult, which must be resolved before any agreement can be inplemented.